2018
DOI: 10.1016/j.jml.2018.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Does dynamic visual noise eliminate the concreteness effect in working memory?

Abstract: Dynamic visual noise (DVN), an array of squares that randomly switch between black and white, interferes with certain tasks that involve visuo-spatial processing. Based on the assumption that the representation of concrete words includes an imagistic code whereas that of abstract words does not, Parker and Dagnall (2009) predicted that DVN should disrupt visual working memory and selectively interfere with memory for concrete words. They observed a reversal of the concreteness effect in both a delayed free rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 49 publications
1
19
0
Order By: Relevance
“…The reason is that Bthe probability of dual coding (and recall) decreases from pictures to concrete words to abstract words because subjects in memory experiments are highly likely to name pictures of familiar objects covertly during learning, somewhat less likely to image to concrete nouns, and least likely to image to abstract nouns^ (Paivio, 1991, p. 265). Paivio and Csapo (1969) observed this ordering in free recall, and the concreteness effect has been observed in many different tests, including recognition (Gorman, 1961), paired associates (Paivio, 1967), serial recall (Walker & Hulme, 1999), serial recognition (Chubala, Surprenant, Neath, & Quinlan, 2018), and free reconstruction of order (Neath, 1997).…”
Section: Accounts Of the Picture Superiority Effectmentioning
confidence: 76%
“…The reason is that Bthe probability of dual coding (and recall) decreases from pictures to concrete words to abstract words because subjects in memory experiments are highly likely to name pictures of familiar objects covertly during learning, somewhat less likely to image to concrete nouns, and least likely to image to abstract nouns^ (Paivio, 1991, p. 265). Paivio and Csapo (1969) observed this ordering in free recall, and the concreteness effect has been observed in many different tests, including recognition (Gorman, 1961), paired associates (Paivio, 1967), serial recall (Walker & Hulme, 1999), serial recognition (Chubala, Surprenant, Neath, & Quinlan, 2018), and free reconstruction of order (Neath, 1997).…”
Section: Accounts Of the Picture Superiority Effectmentioning
confidence: 76%
“…In one of the few studies to directly compare these two tasks using a detection-type analysis, Chubala, Surprenant, Neath, and Quinlan (2018) found that dynamic visual noise, which involves an array of squares that change randomly between black and white several times a second, had a detrimental effect on memory for concrete words when assessed by d′ in serial recognition, but had no effect on memory for concrete words when assessed by proportion correct in serial recall. The lack of an effect of dynamic visual noise on immediate serial recall has been replicated a number of times (e.g., Castellà & Campoy, 2018;Ueno & Saito, 2013).…”
Section: Serial Recall Versus Serial Recognitionmentioning
confidence: 99%
“…On half the trials, two items are transposed in the second list and the task is to indicate if the items are in the same or in a different order as the first list. Chubala, Surprenant, Neath, and Quinlan ( 2018 ) found that performance on the serial recognition test was lower when it was the only test, but higher when half the trials could end in a serial recall test. There is other evidence for a metacognitive component for tasks involving frequency (e.g., Higham, Bruno, & Perfect, 2010 ; Tullis & Benjamin, 2012 ).…”
Section: Discussion Of Experiments 5 Andmentioning
confidence: 99%